THE ANALYSIS OF ROBERT COX'S CRITICAL THEORY: THE INHERENT SUBJECTIVITY AND PURPOSEFUL NATURE OF THEORETICAL FRAMEWORKS - Jundana, Aizza (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2024)
Robert Cox's assertion that “theory is always for someone and for and some purpose